Dynamic equation to estimate the growth in diameter of Pinus montezumae Lamb. in Puebla, Mexico - Tamarit-Urias, Juan Carlos; Quiñonez-Barraza, Gerónimo; García-Cuevas, Xavier; Hernández-Ramos, Jonathan; Monárrez-González, José Carlos (Instituto de Ecología, A.C., 2021)
The diameter at breast height (DBH) has a high correlation with other attributes of the tree and the stand, therefore its modeling is relevant. The objective was to develop a dynamic equation to estimate the growth and increment in DBH of Pinus montezumae trees as a function of age. A sample of 81 trees collected in the "Ixta-Popo" region of Puebla, Mexico was used, and the stem analysis technique was applied. The fit quality of six dynamic equations expressed in algebraic difference (DA) and generalized algebraic difference approach (GADA) was evaluated. The best dynamic equation was selected using statistical criteria and graphic analysis, this is based on the Korf growth model expressed in GADA, which was later adjusted using the artificial variables method, autocorrelation and heteroscedasticity were corrected. This equation presented high precision and accuracy (RMSE = 2.393 cm, Bias = 0.055 cm), it was used to construct a family of growth curves based on the DBH index (IDBH), to determine the current and average annual growth (ICA and IMA), as well as the passage times (PT) by diametric category (DC). For the average condition (IDBH = 37 cm), the CAImax was 1 cm year-1 which corresponds to 9.33 cm of DBH and is reached at 14.8 years. The MAImax was 0.79 cm year-1, which corresponds to 25 cm and occurs at the age of 31.6 years; the average PT was 8.09 years for an interval from 5 cm to 55 cm with DC classes of 5 cm. The equation developed can be part of growth systems and timber yield for the sustainable management of this species in the study area.